Heat Management in Integrated Circuits: On-chip and system-level monitoring and cooling - Ogrenci-Memik, Seda (Materials, Circuits and Devices Series, 2016)
As integrated circuits get smaller and more complex, power densities are increasing, leading to more heat generation. Dealing with this heat is fast becoming the most important design bottleneck of current and future integrated circuits, where power envelopes are defined by the ability of the system to dissipate the generated heat. Thermal effects are forcing chip designers to apply conservative design margins, creating sub-optimal results. At a larger scale, cooling is the second most costly item in the electricity bills of well-designed high-performance computing and data centers, costing 30-50% of the total. Thermal monitoring and management in integrated circuits is therefore becoming increasingly important. This book covers thermal monitoring and management in integrated circuits, with a focus on devices and materials that are intimately integrated on-chip as opposed to in-package or on-board. The devices and circuits discussed include various designs used for the purpose of converting temperature to a digital measurement and actively biased circuits that reverse thermal gradients on chips for the purpose of cooling. Topics covered include an overview of heat in integrated circuits and systems, on-chip temperature sensing, dynamic thermal management, active cooling, and mitigating thermal events at the system-level and above.